2022
DOI: 10.1155/2022/5085143
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis of Knee Joint Function Recovery after Anterior Cruciate Ligament Reconstruction by Accelerated Rehabilitation Surgery

Abstract: Objective. This investigation was undertaken to systematically assess the impact of increasingly rapid recovery treatment on the functional status of the knee following anterior cruciate ligament restructuring. Methods. Computer search from the establishment of the database to March 2022 in China Knowledge Network Database (CNKI), PubMed, EMBASE, ScienceDirect, CochraneLibrary, China VIP Database, Wanfang Database, and China Biomedical Literature Database (CBM). The control group was given only traditional reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In the original study, small sample size, different course of disease, different intervention time, evaluation criteria, and evaluation time were slightly different, which had a certain impact on the evaluation results, thus affecting the results and argumentation intensity. The same idea can be found in the study put forward by Xu et al [41]. They have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
Section: Discussionsupporting
confidence: 79%
“…In the original study, small sample size, different course of disease, different intervention time, evaluation criteria, and evaluation time were slightly different, which had a certain impact on the evaluation results, thus affecting the results and argumentation intensity. The same idea can be found in the study put forward by Xu et al [41]. They have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
Section: Discussionsupporting
confidence: 79%
“…A meta-analysis by Xu et al showed that ERAS can effectively promote knee joint function recovery, reduce patient pain, and decrease postoperative complications. [6] With the application of the ERAS concept in elderly patients undergoing orthopedic joint replacement surgery, there has been increasing research on improving the safety and effectiveness of postoperative care and recovery. [34,50] This systematic review and meta-analysis aimed to investigate whether ERAS can reduce postoperative pain, accelerate joint function recovery, and decrease the incidence of postoperative complications in elderly patients undergoing joint replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the included studies was evaluated using the modified JADAD scoring scale. [6] The modified JADAD scoring method was based on a random sequence of literature generation, assigned hidden or blind, and whether participants described withdrawal or withdrawal details. A total score of 4 to 7 is rated as high-quality research, and 1 to 3 as low-quality research.…”
Section: Methodsmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%